RELATION WRITING–BODY FLUIDS AS A POSSIBILITY OF A FEMALE IDENTITY CONSTRUCTION IN TWO POEMS OF NOCHES DE ADRENALINA (1981) - Calderón Muchotrigo, Estefany (2020)
The present work seeks to focus on the rhetorical analysis of two poems of Noches de adrenalina (1981) by Carmen Ollé. On this occasion, the objective is to analyze the relationship between writing and body fluids. It is held that both are actions that are generated within the body of the subject (head-organs), and that at the moment of externalizing them, they allow a liberation and construction of the feminine identity. For this we will take the contributions of Stefano Arduini and Giovanni Bottiroli in order to give an account of the rhetorical figures and the world view that supports our initial approach.